Antibacterial activity and preservative properties of thinned young apples extracts for fish flesh. Issue 2 (1st August 2017) - Zhang, Juan; Chen, Weiqi; Li, Shuai; Xue, Zhanfeng; Zheng, Wenlong; Guo, Yurong
Abstract: The content of polyphenols from thinned young apples (TYA) is higher than that in ripe apples. Polyphenols have been reported to show a variety of biological activities. Antibacterial activities were tested at three different percentages of TYA extracts of 0.05, 0.1, and 0.2% on 53 bacterial strains, and the validity of minimum inhibitory concentration (MIC) was investigated. To evaluate preservative properties of TYA extracts for fish cubes at 4 °C in refrigerator, fish cubes were treated with 0.1% TYA extracts and potassium sorbate (PS) solution (0.075 g/kg fish flesh). Results revealed that TYA extracts showed significant antibacterial activity against 18 strains out of selected 53 bacterial ones, with MIC values ranging from 256 to 2, 048 µg/mL. The 0.1% TYA extracts can inhibit the increase of pH value and control malondialdehyde more efficiently than PS at the same concentration. Interestingly, The 0.1% TYA extracts also suppressed total volatile basic nitrogen value and reduced total bacteria counts only in storage for 2 days than PS. Practical applications: China Association for Ethical Studies has approved the study, and all experiments were performed per the approval of the Institutional Animal Care and Use Committee.